Education Level and Illness Perception in Parents of School-Aged Children with Thalassemia Major - Fathaddin, Asma Teja asih; Yamin, Ahmad; Mardhiyah, Ai (Sarana Ilmu Indonesia (salnesia), 2025)
The education level of parents shapes their mindset and perception of illness, significantly influencing their child’s illness perception, coping strategies, psychological well-being, medication adherence, and physical functioning. This study aimed to identify the relationship between the education level and illness perception of parents with children suffering from thalassemia major. This study used secondary data from previous research conducted within the institution that had not been published. It employed a descriptive analytical method with a cross-sectional approach. The sample was selected using purposive sampling, involving 90 parents as participants. Data were collected using demographic data and the Illness Perception Questionnaire-Revised (IPQ-R) instrument. Data analysis was performed using univariate and bivariate methods, with the chi-square test applied for the bivariate analysis. Among all subject, the majority (51,1%) had a secondary education level. A total of 53,3% of parents had a positive illness perception. The relationship between education level and illness perception was not statistically significant (p-value = 0,813). This study indicated that parents' education level did not have a significant impact on their illness perception. Formal education was not the primary factor influencing the illness perception of parents with school-age children with thalassemia major in Bandung.